Nitric oxide radical suppresses replication of wild-type dengue 2 viruses in vitro - Weerawan Charnsilpa (2018)
Nitric oxide is well accepted as one of the defenses for inhibiting viral dissemination. Macrophages and cells in the macrophage lineage are professional nitric oxide producers which subserve as target for dengue virus. The interaction between nitric oxide and dengue virus in such target cell is unknown. In this report, the impact of nitric oxide on infectious dengue virus serotype 2 production and RNA replication was investigated in vitro. Primary isolates of dengue virus serotype 2 from dengue patients were replicated in mouse neuroblastoma cells in the presence of an exogenous nitric oxide donor, s-nitroso-N-acethyl-pennicillamine, SNAP, at the concentration of 50 or 75 or 100 μM. Nitric oxide inhibited viral replication in a dose and a multiplicity of infection dependent manner. Nitric oxide from 50 and 75 μM SNAP delayed and suppressed replication of dengue virus isolates while higher concentration of nitric oxide, 100 μM SNAP, completely inhibited production of infectious particles up to 36 hr study. Twenty-four out of forty tested isolates, 60%, were susceptible to 50 μM SNAP inhibitory effect. The mechanism of inhibition was investigated at the level of RNA synthesis and was found that RNA production was suppressed which correlated to production of the infectious particles. Down-regulation of the RNA synthesis resulted in reduction of protein synthesis which was detected by lower level of NS1 protein synthesis using immunoblotting. In conclusion, nitric oxide from exogenous nitric oxide donor down regulated replication of dengue virus serotype 2 isolates from dengue patients. The suppression was clearly shown at the level of viral RNA and protein synthesis resulting in reduction of viral progenies production. This phenomenon implies that nitric oxide may serve as a defense which diminishes viral load in patients. © 2005 Wiley-Liss, Inc.